Art and Economics in the City New Cultural Maps - Benincasa, Caterina; Neri, Gianfranco; Trimarchi, Michele (transcript Verlag, 2019)
Emerging forms of alternative economy are changing the structure of society, redefining the relationship between centre and periphery in the urban fabric. In this context, the arts can play a crucial role in formulating a concept of complex and plural citizenship: This economic, social and cultural paradigm has the potential to overcome the conventional isolation of the arts and culture in ivory towers, and thereby to gradually make the urban fabric more fertile. This volume faces such sensitive issues by collating contributions from various disciplines: Economists, sociologists, urbanists, architects and creative artists offer a broad and deep assessment of urban dynamics and their visions for years to come.
Description based on print version record.
KU Select 2018: HSS Frontlist Books
Keywords: Social Science / Sociology; Social sciences; Electronic books